KENAIKAN MUKA AIR LAUT PERAIRAN SUMATERA BARAT BERDASARKAN DATA SATELIT ALTIMETRI JASON-2 - Khasanah, Isna Uswatun (Badan Informasi Geospasial in Partnership with MAPIN, 2017)
The phenomenon of the sea level rise caused by many factors, one of which is global warming. Coastal areas are most vulnerable regions affected by sea level rise. Therefore, the information of sea level rise are used as consideration and policy-making on development plans for coastal areas like in West Sumatera Waters. The aims of this research are to identify the quality of Satelit Altimetry Jason-2 Data in West Sumatera Waters and to analysis the information of sea level rise of West Sumatera sea based on satelit altimetry Jason-2 data. Sea Level Rise in West Sumatera Water are identified by several steps, begin with collecting satellite altimetry Jason-2 data from 2008 to 2015 years. Then extraction Sea Surface Height (SSH) value of Â binary GDR data from Jason-2 by post processing to eliminate the geophysic errors, furthermore extraction undulation geoid value and calculating the Sea Level Anomaly (SLA) value. To identify the sea level rise value used linear regression analysis on the SLA data. Â The results of this research shown the existence of satellite altimetry Jason-2 data is 92.91%. The mean sea level rise in West Sumatera Waters during th period 8 year is 6.88 mm, and mean sea level rise of West Sumatera sea is 0.86 mm/year.